2021
DOI: 10.3390/biomedicines9111712
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of a Novel Selective EP4 Prostaglandin Receptor Agonist on Treatment of Critical Size Femoral Bone Defects in a Rat Model

Abstract: Difficulties in treating pseudarthrosis and critical bone defects are still evident in physicians’ clinical routines. Bone morphogenetic protein 2 (BMP-2) has shown promising osteoinductive results but also considerable side effects, not unexpected given that it is a morphogen. Thus, the bone regenerative potential of the novel selective, non-morphogenic EP4 prostaglandin receptor agonist KMN-159 was investigated in this study. Therefore, mineralized collagen type-1 matrices were loaded with different amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…In contrast the local release of a selective EP4-prostaglandin receptor agonist from a mineralized collagen scaffold can increase bone formation. 146 Hayashi et al demonstrated that titanium-coated rough-surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4-prostaglandin receptor agonist. 147 Bone Morphogenetic Protein 2 is a clinically approved growth factor for facilitating bone regeneration.…”
Section: Stimulating An Atrophic Environment Around Implants Towards ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast the local release of a selective EP4-prostaglandin receptor agonist from a mineralized collagen scaffold can increase bone formation. 146 Hayashi et al demonstrated that titanium-coated rough-surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4-prostaglandin receptor agonist. 147 Bone Morphogenetic Protein 2 is a clinically approved growth factor for facilitating bone regeneration.…”
Section: Stimulating An Atrophic Environment Around Implants Towards ...mentioning
confidence: 99%
“…Nonsteroidal anti‐inflammatory drugs and corticosteroid reduce the inflammatory reaction and subsequent bone formation. In contrast the local release of a selective EP4‐prostaglandin receptor agonist from a mineralized collagen scaffold can increase bone formation 146 . Hayashi et al demonstrated that titanium‐coated rough‐surfaced implants had an increased implant fixation strength, if osteoporotic animals were treated with a selective EP4‐prostaglandin receptor agonist 147 …”
Section: How Can We Modulate the Inflammatory And Foreign Body Respon...mentioning
confidence: 99%
“…Beyond that, PGE2 has been functionally implicated in endochondral development by in vitro studies with the murine pro-chondrogenic cell line ATDC5 and rat periosteum cultures, in which COX-2 inhibition was reported to reduce Col10a1 and Alpl gene expression [20], while in turn PGE2 stimulated Col10a1 expression [21]. Moreover, an impaired endochondral bone formation and fracture healing was apparent in COX-2 loss-of-function models in mice, rats, and rabbits that could be rescued by PGE2 or an EP4 agonist [22][23][24][25][26][27]. While altogether, this may indicate a prohypertrophic activity of PGE2, a large body of opposing studies reported that PGE2 or EP4 activation decreased Col10a1 and Alpl expression, ALP activity, and mineralization in chick or murine limb bud mesenchymal cells and growth plate chondrocytes [28][29][30][31][32], attributing an antihypertrophic activity to PGE2.…”
Section: Introductionmentioning
confidence: 99%